Analytical assessment of the efficacy and safety of pudendal nerve block in post-haemorrhoidectomy pain management - Nitin Kalaskar; Anveerbhadra Allad; Dharaneesh DVS (Asian Journal of Medical Sciences, 2025)
Background: Post-hemorrhoidectomy pain is a significant challenge, often necessitating the use of multiple analgesics, including opioids, which come with potential side effects such as nausea, constipation, and dependency. Alternative approaches like regional nerve blocks, including the pudendal nerve block (PNB), have been proposed to alleviate pain management with fewer side effects. Aims and Objectives: The current study was designed to compare the efficacy and safety of PNB over standard analgesia in Basaveshwar Teaching and General Hospital, Gulbarga. Materials and Methods: A randomized controlled trial was conducted involving patients undergoing hemorrhoidectomy. Participants were divided into two groups: One receiving PNB in addition to standard analgesics, and the other receiving only standard analgesics. Pain scores were assessed using the visual analog scale at regular intervals post-surgery. Secondary outcomes included the need for additional analgesics, hospital stay duration, and complications. Statistical analyses were performed to determine the significance of differences between groups. Results: Patients receiving PNB reported significantly lower pain scores compared to the control group (P<0.05). The use of additional analgesics was reduced by 30%, and no severe complications related to the nerve block were observed. Hospital stay duration was also slightly shorter in the intervention group. Conclusion: The PNB is an effective and safe adjunct for post-hemorrhoidectomy pain management. Its ability to reduce pain and decrease reliance on systemic analgesics makes it a promising alternative to traditional approaches.